Making Climate Change Mitigation and Adaptability Real in Africa with Conservation Agriculture - Gonzalez-Sanchez, E.J (2018)
In this report, the authors have gathered essential information on how the agricultural sector can respond to climate change through Conservation Agriculture (CA). This document aims to serve as a basis for decision-making based on science and agricultural experimentation in Africa.